Pengaruh persepsi keadilan kompensasi dan motivasi terhadap kinerja karyawan pada PT. Jambi Distribusindo Rayat - Aidel Oktaviani; Shofia Amin; Rts. Ratnawati (Jurnal Dinamika Manajemen, 2021)
This study examines the effect of perceived fairness of compensation and motivation on employee performance. The sample of this research is 60 employees at PT. Jambi Distributionsdo Raya. The data collection method used a questionnaire and was measured by a Likert scale. The data testing technique used in this study includes instrument testing (validity test, reliability test), multiple linear regression analysis t-tests, F test, and coefficient of determination test (R2) with the help of SPSS application. Based on this research, it can be concluded that it partially shows that compensation fairness has a positive and significant effect on employee performance and motivation has a positive and significant impact on employee performance. Simultaneously, compensation justice and reason positively and significantly affect employee performance at PT. Jambi Distributionsdo Raya